Diminished: Canadian Women's Experiences of Electroshock - van Daalen-Smith, Cheryl; Hagen, Brad; Breggin, Peter (Atlantis, 2015)
“Diminished” is the result of a two-year feminist inquiry into the gendered experience of electroconvulsive therapy (ECT) in Canada. This paper focuses on seven women’s experiences with electroshock and how it affected their lives. It raises pressing questions for Canadian feminists about the apparent dispensability of women’s minds, with the purpose being to re-ignite feminist interest in women’s experiences of psychiatry in general and the damaging effects of electroshock in particular.